How to explain Wage Growth Slowdown in Austria? A sectoral-panel analysis of collectively bargained minimum wages - Philipp Gerhartinger; Philipp Haunschmid; Dennis Tamesberger (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2017)
This paper studies the relationship between union power, unemployment and wages. We find many theoretically well-established links suggesting that unemployment negatively affects bargaining power. As an empirical strategy we use Austrian data from 1966 until 2015 on the development of collectively bargained minimum wages. Such data directly reflects the result of a bargaining process between unions and employer organizations, and enables to show the link between bargaining power and unemployment. Moreover, it allows for further discussion on the potential influence of other macroeconomic and institutional variables, such as trade openness and union density.
Keywords: 330; WAGE GROWTH; MINIMUM WAGES; UNEMPLOYMENT; UNIONS; BARGAINING POWER